Anthracene adamantylbisurea receptors: switching of anion binding by photocyclization. Issue 49 (9th December 2015) - Blažek Bregović, Vesna; Halasz, Ivan; Basarić, Nikola; Mlinarić-Majerski, Kata
Abstract: Anion binding of adamantane bisurea receptors 1 –4 bearing anthracene chromophores was investigated in DMSO solution by UV–vis and fluorescence titrations. All derivatives form stable complexes with F − (K1:2 ≈10 5 –10 6  M −2 ), AcO − (K1:1 ≈10 3  M −1 ), and H2 PO4 − (K1:1 ≈10 3 –10 4  M −1, K1:2 ≈10 5 –10 6  M −2 ). Photochemical reactivity of 1 –4 in the [4π+4π] photocyclizations was also investigated. Anthracene 1 is photochemically stable, 3 and 4 undergo reaction giving mixture of products, but 2 reacts selectively yielding only cyclic product 5 . Product 5 was isolated and characterized by X-ray analysis. Cyclic receptor 5 also binds anions but forms complexes with different stability constants than its opened analogue 2 . Anthracene 2 forms more stable complex with H2 PO4 −, whereas cyclic receptor 5 forms the most stable complex with AcO − (K1:1 >10 6  M −1 ). Graphical abstract: